Derajat Stres Mahasiswa Baru Fakultas Kedokteran Ditinjau Dari Tingkat Penyesuaian Diri Terhadap Tuntutan Akademik - Bania Maulina; Dwi Retno Sari (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
People encounter many changes in the first year of college. It was related to adjustment’s problems, which was a serious problem that must be faced when entered college. Adaptation to new environment can make individual experienced stress. The various studies have shown that medical students experienced stress more higher than non-medical program students. Students who are experiencing extreme stress or depressed require serious attention cause it can have an adverse effect on learning process, achievement and even intent to suicide. This research involved 49 medical students. It took to determine the correlation between level of adjustment to academic demands and stress degree on new students in Faculty of Medicine, Islamic University of North Sumatra, T.A 2016-2017. Student Adaptation to College Questionnaire (SACQ) and Kessler Psychological Distress Scale (K10 Test) were used to collect relevant data on adjustment rates and stress levels. Data were analyzed by using Spearman correlation test. The results showed that there was a significant negative correlation between adjustment rates to academic demands with stress level on new students with p value of 0.001 (p <0.05) and r value of -0.697.